Enhancing Social Entrepreneurship Model for Social Entrepreneurs: A Case of AL-FALAH Foundation - Fakhrul Anwar, Zainol; Wan Norhayate, Wan Daud; Zulhamri, Abdullah; Mohd Rafi, Yaacob (2014)
This study examines the importance of enhancing a social entrepreneurship model for social entrepreneurs on the context of urban poverty. This study begins with the introduction of brief background of AL-FALAH Foundation. A detail of AL-FALAH Foundation’s organization structure, vision, mission and its functions are described thoroughly. The study documents the physical characteristics and environment of the social entrepreneurship of AL-FALAH Foundation. We measure three key characters of social entrepreneurship – innovation, proactiveness, and risk taking on the current practice of organization. We found that AL-FALAH Foundation is being proactively in achieving their mission. Specifically, AL-FALAH can be considered as innovation, proactiveness and risk taking in being efficient financially. The organization focuses on elevating their members’ socio-economic living standard through shares and other profitable investments. This study implies that social entrepreneurship model can be effectively practiced in the corporate setting which may leverage the networks in a moderate competitive business environment.